Crystal structure of tricyclohexyl[4-(4H-1,2,4-triazol-4-yl)-benzoato-κO]tin(IV), C27H39N3O2Sn - Qing, Jingjing; Tian, Jie; Deng, Xin; Zhang, Fuxing (Zeitschrift für Kristallographie. New crystal structures, 2024)
Sn, monoclinic, (no. 14), = 10.3317(6) Å, = 15.8067(9) Å, = 16.5497(9) Å, = 90.5380(10) , = 2702.6(3) Å , = 4, ) = 0.0370, w ) = 0.0954, T = 296(2) K.